'It is, that's all.': J. M. Coetzee's Life & Times of Michael K (1983) and the cinema of Alain Robbe-Grillet. Issue 1 (2nd January 2023) - Webster, Guy
ABSTRACT: The notebooks that accompany J. M. Coetzee's early drafts of The Life & Times of Michael K (1983) reveal the importance of cinematic modes of representation for Coetzee's conception of the eponymous Michael K. With reference to early drafts of the novel, this paper argues that Michael K's characterisation is particularly influenced by Alain Robbe-Grillet's filmmaking practices. Specifically, this article illustrates the importance of Robbe-Grillet's treatment of subjectivity and objectivity for Coetzee's experimentation with modernist modes of writing. Coetzee's experiments with cinematic form during the drafting process illustrate the ways in which he navigates his fidelity to modernism's formalist values in relation to the political and literary concerns that encircle him as an author in apartheid-era South Africa. By analysing the implicit and explicit influence of Robbe-Grillet's aesthetic values as a filmmaker on Coetzee's writing, this article illustrates the importance of acknowledging cinematic modes of representation in Coetzee's fidelity to the nouveau roman, and his continuing investigation of modernism during this era.